2019
DOI: 10.1186/s12938-019-0743-1
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics simulation of reversible electroporation with Martini force field

Abstract: BackgroundAfter the discovery of membrane-reversible electroporation decades ago, the procedure has been used extensively in biology, biotechnology and medicine. The research on the basic mechanism has increasingly attracted attention. Although most research has focused on models that consider all atomic and molecular interactions and much atomic-level information can be obtained, the huge computational demand limits the models to simulations of only a few nanometers on the spatial scale and a few nanoseconds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Coarse-grained (CG) approaches have the advantage of dealing with simplified molecular models, leading to larger and longer simulations with less computational efforts . The MARTINI CG force field has been proven as a very useful tool for probing interactions of chemical compounds with biological membranes (including antimicrobial peptides), exploring membrane phase transitions, pore formation, membrane fusion and disruption, and electroporation phenomena. Here, we use CG MD simulations to study the interaction of antiseptics belonging to three chemically diverse groups of CAs (biguanidine, quaternary amine, and pyridine derivatives) with the model bacterial membrane consisting of phosphatidylethanolamine (POPE) and phosphatidylglycerol (POPG) in a 3:1 ratio.…”
Section: Introductionmentioning
confidence: 99%
“…Coarse-grained (CG) approaches have the advantage of dealing with simplified molecular models, leading to larger and longer simulations with less computational efforts . The MARTINI CG force field has been proven as a very useful tool for probing interactions of chemical compounds with biological membranes (including antimicrobial peptides), exploring membrane phase transitions, pore formation, membrane fusion and disruption, and electroporation phenomena. Here, we use CG MD simulations to study the interaction of antiseptics belonging to three chemically diverse groups of CAs (biguanidine, quaternary amine, and pyridine derivatives) with the model bacterial membrane consisting of phosphatidylethanolamine (POPE) and phosphatidylglycerol (POPG) in a 3:1 ratio.…”
Section: Introductionmentioning
confidence: 99%
“…[53][54][55] Second, the electric field values used in the atomistic studies are in the range of 0.05-10.2 V nm À1 . [25][26][27][28][29] The electric fields used in the experiments typically are on the order of 10 À3 V nm À1 23,56,57 but may reach a value as high as 0.08 V nm À1 . 58 The typical difference between the electric field values in simulations and experiments likely arises from the fact that the numerical studies are performed in an idealized system lacking multiple lipid species, heterogeneities and ionic concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental studies have revealed electric field-induced shape transformation in giant unilamellar vesicles, [16][17][18][19][20][21] shape instabilities in membrane tubules, 22 phase separation in multicomponent membranes, 6,23 and lipid flows. 24 On the modeling front, atomistic studies [25][26][27][28][29][30] and continuum studies [31][32][33] have provided insights into the electroporation and shape transformations in vesicles.…”
Section: Introductionmentioning
confidence: 99%
“…With the growth of computer technology, the molecular dynamics (MD) technique has shown tremendous promise and provides a significant insight into the process of electroporation. Accumulated evidence suggested that the rate of pore formation of phospholipid bilayers increases remarkably when exposure to a sufficiently strong electric field [19][20][21][22] . Most recently, MD simulation has also been successfully utilized to elucidate the experimental findings of the sustainable permeability of cell membranes induced by lipid peroxidation 23 .…”
Section: Introductionmentioning
confidence: 99%